Exploit The Grammarly Application in English Language Program Writing Skills: In Perceptions - Xena, Esmeralda Dida Ayu Amindexa; Setyawan, Mochamad Ardi; Anwar, Saiful; Pambayun, Rizki Nurfida (English Language Teaching Methodology, 2025)
In recent years, educational technology has transformed how students develop academic writing skills. Digital tools not only improve efficiency but also enhance learning through interactive and adaptive feedback. Among these innovations, artificial intelligence–based writing assistants provide immediate feedback, linguistic accuracy, and stylistic improvement. Grammarly, in particular, has gained attention in higher education for its accessibility, user-friendly interface, and ability to address grammar, vocabulary, and coherence. Its widespread use among non-native English-speaking students underscores the need to understand how learners perceive and utilize such tools.This study examines English Education students’ perceptions of Grammarly at Universitas 17 Agustus 1945 Banyuwangi as a tool to enhance academic writing. Using a qualitative descriptive approach and purposive sampling, ten students participated in semi-structured interviews. The research explored usage frequency, perceived benefits, and limitations.Results indicate that students generally view Grammarly positively, especially for improving grammar, sentence structure, and vocabulary. Features like real-time feedback, tone detection, and clarity suggestions are valued for aiding learning. However, concerns include occasional contextual inaccuracies and the risk of overreliance, potentially reducing self-editing and critical thinking skills.The study concludes that Grammarly should supplement, not replace, teacher feedback or manual revision, and recommends further research on its long-term impact and integration with other writing resources.